Methylphenidate improves some but not all measures of ATTENTION, as measured by the TEA-Ch in medication-naïve children with ADHD - ROBERTSON, IAN; FITZGERALD, MICHAEL; GILL, MICHAEL (My University, 2013)
The Test of Everyday Attention for Children (TEA-Ch) is a reliable neuropsychological assessment of attention control in children. Methylphenidate (MPH) is an effective treatment to improve attentional difficulties in children with attention deficit/hyperactivity disorder (ADHD). Previous studies investigating the effects of MPH on attention performance of children with ADHD have produced mixed results and prior MPH usage may have confounded these results. No previous study has tested the effects of MPH on the entire TEA-Ch battery. This study investigated the effects of MPH on attention performance using the entire TEA-Ch in 51 medication-naïve children with ADHD compared with 35 nonmedicated typically developing children. All children were tested at baseline and after 6 weeks: The children with ADHD were medication-naïve at baseline, received MPH for 6 weeks and were tested whilst on medication at the second testing session. A beneficial effect of MPH administration was found on at least one subtest of each of the three forms of attention (selective, sustained, and attentional control) assessed by the TEA-Ch, independent of practice effects. MPH aided performance on the TEA-Ch tasks that were inherently nonarousing and that might require top-down control of attention. It is recommended that the TEA-Ch measures—Sky Search Count (selective attention),Score! (sustained attention), Creature Counting Time Taken for older children (attentional control), and Same Worlds (attentional control) be prioritized for use in future pharmacological studies using MPH.
PUBLISHED
(305) PMID: 23639119 ABSTRACT: The Test of Everyday Attention for Children (TEA-Ch) is a reliable neuropsychological assessment of attention control in children. Methylphenidate (MPH) is an effective treatment to improve attentional difficulties in children with attention deficit/hyperactivity disorder (ADHD). Previous studies investigating the effects of MPH on attention performance of children with ADHD have produced mixed results and prior MPH usage may have confounded these results. No previous study has tested the effects of MPH on the entire TEA-Ch battery. This study investigated the effects of MPH on attention performance using the entire TEA-Ch in 51 medication-naïve children with ADHD compared with 35 nonmedicated typically developing children. All children were tested at baseline and after 6 weeks: The children with ADHD were medication-naïve at baseline, received MPH for 6 weeks and were tested whilst on medication at the second testing session. A beneficial effect of MPH administration was found on at least one subtest of each of the three forms of attention (selective, sustained, and attentional control) assessed by the TEA-Ch, independent of practice effects. MPH aided performance on the TEA-Ch tasks that were inherently nonarousing and that might require top-down control of attention. It is recommended that the TEA-Ch measures-Sky Search Count (selective attention),Score! (sustained attention), Creature Counting Time Taken for older children (attentional control), and Same Worlds (attentional control) be prioritized for use in future pharmacological studies using MPH.
Keywords: Methylphenidate; Attention deficit/hyperactivity disorder; Genes & Society; Neuroscience; ADD/ADHD; ADD/ADHD; ADHD; ADHD; ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD); Adolescent Psychiatry; Attention Deficit Hyperactivity Disorder (ADHD); CHILD PSYCHIATRY; COMMUNITY PSYCHIATRY; CONSULTATION LIAISON PSYCHIATRY; CONSULTATION-LIAISON PSYCHIATRY; DISORDER ADHD; GENERAL HOSPITAL PSYCHIATRY; LIAISON PSYCHIATRY; METHYLPHENIDATE; Neuropsychiatry; Neuropsychiatry; PSYCHIATRY; Psychiatry; Psychiatry; TEA-Ch; TRAINEES IN PSYCHIATRY; adult ADHD; child and adolescent Psychiatry; neurodevelopmental psychiatry; non-ADHD Siblings